ANALYSIS OF UNSTEADY LIQUID MOTION IN CIRCULAR CYLINDRICAL SHELLS FOR COMPLEX SCHEME INCLUDING SEVERAL RINGS - F V Rekach (Structural Mechanics of Engineering Constructions and Buildings, 2016)
He analysis of parameters of the unsteady fluid motion for complex circuits containing several circular rings is given in a paper. The author has set the task to carry out the calcula- tions of long hydraulic circuits with the presence of several circular rings included in the ge- ometry of the outline with different diameters of the pipelines with the specified estimated consumer spending with many points of branching pipelines. Thermal circuit of Nizhniy Novgorod city is adopted in the enlarged view.